Stock price reaction when Covid -19 exist: moderating by firm’s operating cash flow - Nugroho, Dwiyanjana Santyo; Pertiwi, Meilani Intan (Penerbit Universiti Kebangsaan Malaysia, 2021)
COVID-19 has been declared a global pandemic by the WHO, rendering the stock markets volatile. Investors predict that the pandemic can be a threat to a company's cash flow, whereas managers use the last year’s financial condition to defend their stock price. We evaluate whether the company's operating cash flow moderates the company's financial condition and stock price reactions, in addition to making a comparison between the period before and during the COVID-19 pandemic using Difference in Difference. The regression analysis model used is a random effect model. The objects of this research are the hotel, tourism, restaurant, and retail trade sub-sector companies in the first quarter and second quarter of 2020, and 2019 and 2018 annually. We found that none of the firm's financial condition affected the stock's price reaction. We also found that operating cash flow strengthens the relationship between cash and ROA to the stock price. The results of this study further imply that the COVID-19 pandemic caused a significant stock price reaction when compared between the time before and during the COVID-19 disaster in Indonesia. The current study is hoped to contribute towards supporting the government in formulating policies to stimulate the currently-slumping economy. This study can also assist the investors in preparing their analysis to determine whether what action they should take in regards to their stocks, considering that our research implicitly reflects the development of conditions in several industrial sectors.